Effects of mixture of wood vinegar and sulfonylurea-based herbicides on the control of mixed weed flora and the yield of transplanted rice (Oryza sativa L.) - Rico, Cyren M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2007)
The effects of mixed treatments of wood vinegar (WV) and sulfonylurea-based herbicides on the weed control and the yield and yield components of transplanted rice were investigated. The herbicides tested were: pyrazosulfuron-ethyl+esprocarb [PSE; ethyl-5-[(4,6-dimethoxypyrimidin-2- ylcarbamoyl)sulfamoyl]-1-methylpyrazole-4-carboxylate+S-benzyl (RS)-1,2-dimethylpropyl (ethyl)thiocarbamate], pyrazosulfuron-ethyl+molinate [PSM; S-ethyl azepane-1-carbothioate] and pyrazosulfuron-ethyl+mefenacet [PSMF; 2-(1,3-benzothiazol-2-yloxy)-N-methylacetanilide]. Five treatments were used: 1 ) recommended (RH: 100%), 2) half-recommended (HRH: 50%), 3) HRH + 500 (1 mL wood vinegar 500 mL-1 water), 4) HRH + 1000 (1 mL wood vinegar 1000 mL-1 water) and 5) untreated control. Results showed that only PSM significantly increased the efficacy of HRH while PSE and PSMF already obtained high efficacy in HRH alone. Higher rice yield was obtained in the HRH plus wood vinegar treatments of PSM. On the other hand, a decrease in rice yield was observed in the HRH plus wood vinegar treatments of PSE and PSMF compared with the RH and HRH treatments. Data on yield components showed no significant variations in values among the treatments. No clear trend for grain appearance and nutritional quality was observed.